Juridical Analysis of the Criminal Act of Sexual Violence of Children from the Perspective of Criminal Law in Indonesia - Ismayana Ismayana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study focuses on analyzing the enforcement of criminal law in cases of sexual intercourse with children in Indonesia, with particular attention to the balance between legal certainty and victim-oriented justice. The research aims to examine the extent to which criminal justice practices have accommodated the interests of child victims, to identify the limitations of a retributive approach, and to propose an alternative conceptual framework based on the theory of Dignified Justice.This research employs a normative legal research method using statutory, conceptual, and theoretical approaches, complemented by secondary empirical analysis of Decision of the Kuningan District Court Number 5/PID.SUS/2024/PN.KNG. Data were collected through a literature review of primary, secondary, and tertiary legal materials, including legislation, court decisions, reputable international journals, and relevant academic literature. Data validity was ensured through source triangulation and theoretical triangulation to maintain consistency, reliability, and analytical accuracy. The findings indicate that sentencing in this case reflects normative firmness and proportionality in accordance with positive law. However, the criminal justice process remains dominated by an offender-oriented approach and has not explicitly incorporated victim recovery mechanisms, such as restitution and psychological rehabilitation. As a result, the justice delivered tends to be merely symbolic from the victim’s perspective. This study also identifies that sexual crimes against children are influenced by a combination of internal offender-related factors and structural external factors. From the perspective of Dignified Justice, this research emphasizes the urgency of reformulating child criminal law to integrate offender punishment, victim recovery, and structural prevention as unified objectives of criminal justice.